2017
DOI: 10.14260/jemds/2017/542
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Conventional and Automated Blood Culture in the Early Detection of Bacterial Pathogens

Abstract: BACKGROUNDBlood culture is a critical tool in the microbiological laboratory, which detects and identifies microorganisms in the blood along with antibiotic susceptibility and has considerable prognostic significance by suggesting appropriate antibiotic therapy. Automated blood culture systems are replacing conventional methods and must be comparatively studied to elucidate the benefits and advantages. The present study compares a recently installed BacT/ALERT automated system with the conventional method with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…It showed that yield of bacteria by automated method was 100% (29/29) as compared to conventional method which had 89.7% (26/29) yield of bacteria. These findings are similar to a study that showed yield of bacteria by automated and conventional methods were 96.9% and 80% 9 . Our study showed among the isolated bacteria, Klebsiella spp (62.0%) was predominant, followed by Acinetobacter spp (21.0%), Escherichia coli and Pseudomonas spp (6.8%) each and Serratia spp (3.4%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It showed that yield of bacteria by automated method was 100% (29/29) as compared to conventional method which had 89.7% (26/29) yield of bacteria. These findings are similar to a study that showed yield of bacteria by automated and conventional methods were 96.9% and 80% 9 . Our study showed among the isolated bacteria, Klebsiella spp (62.0%) was predominant, followed by Acinetobacter spp (21.0%), Escherichia coli and Pseudomonas spp (6.8%) each and Serratia spp (3.4%).…”
Section: Discussionsupporting
confidence: 91%
“…The ideal blood culture system assembles the maximum yield of pathogen as early as possible in order to have maximum influence on patient management 7 . Different comparative studies including ours have reported different percentages of bacterial growth along with yield of bacteria by both methods 8,9 . In case of life threatening conditions like neonatal sepsis, irrational use of antibiotics have swayed the sensitivity pattern of microbes, which are evident in several recent studies thus making the use of unconventional drugs compulsory and lifesaving 10,11 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Technological developments resulted in the accessibility of diverse systems, each appealing to be greater in different facets. 7 Drawbacks of the conventional method require a better diagnostic tool with higher yield and speed.…”
Section: Introductionmentioning
confidence: 99%